ANALISIS EFEKTIVITAS RUANG HENTI KHUSUS SEPEDA MOTOR PADA SIMPANG BERSINYAL DI KOTA SEMARANG - Reska Ayu Yuniar M.; Raisha El Kahira; Ismiyati Ismiyati; Bagus Hario Setiadji (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Based on WHO research in 2010 shows growth of motorcycles in Indonesia reached 60 million units with proportion of 83% compared to other vehicle types (Helmi, 2015). Motorcycles are the smallest vehicle that has the mobility and maneuverability of high movement. At the time of the green phase, motorcycles struggling to get out from the intersection and continue the journey. The movement of motorcycle can cause conflict with the car or with other motorcycles. Studies conducted by M. Idris in Bandung in 2007 produced Advanced Stop Lines (ASL) for motorcycles can reduce traffic conflicts up to 72% and 11-12% streamlined of traffic flow (Faundra, 2012). The purpose of this research was to analyze the effectiveness of the Advanced Stop Lines (ASL) for motorcycles at the intersection with different characteristics in Semarang. The parameters used in this research are existing conditions, real conditions, the percentage of occupancy ASL, and hypothesis testing comparison. The research method is done by simulating ASL in three arms at signalized intersections in Semarang. Hypothesis test comparison is done by using the hypothesis H0 if the volume of vehicles before they are applied equally to the post applied ASL. The results of this study can be concluded that based on the hypothesis test comparison there is only one research location hypothesis is accepted. ASL for three research locations affect the number of vehicle volume, long queues, and Degree of Saturation. ASL has not seen optimal of the three research locations. It because of geometry conditions are different on three research location , improper lane width, the existence of the island roads, and a left turn on red lane. To be more optimal use of ASL should refers to the rules applicable at the selection of sites that will be imposed ASL.